2018
DOI: 10.1073/pnas.1721420115
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory inertial focusing in infinite microchannels

Abstract: SignificanceInertial microfluidics is a widely used technology which enables label-free manipulation of particles in microchannels. However, this technology has been limited to bioparticles larger than RBCs, due to the strong correlation between the inertial lift forces and the particle size. This paper presents a method to extend the capabilities of inertial microfluidics to smaller bioparticles, of which a plethora of clinically relevant types exist in the human body. Therefore, this method can be integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…However, an oscillatory flow strategy enables microchannels to have an infinite effective length, enabling the inertial focusing of small particles in relatively short channels. This was demonstrated by Mutlu et al in 2017, who used a 10–20 Hz oscillatory flow to focus a variety of particles as small as 500 nm in 10 s . In addition to focusing, other modes of self‐assembly are possible in oscillatory inertial microfluidic systems …”
Section: Pulsatile Flows In Microfluidic Processesmentioning
confidence: 99%
“…However, an oscillatory flow strategy enables microchannels to have an infinite effective length, enabling the inertial focusing of small particles in relatively short channels. This was demonstrated by Mutlu et al in 2017, who used a 10–20 Hz oscillatory flow to focus a variety of particles as small as 500 nm in 10 s . In addition to focusing, other modes of self‐assembly are possible in oscillatory inertial microfluidic systems …”
Section: Pulsatile Flows In Microfluidic Processesmentioning
confidence: 99%
“…Due to the symmetry of the velocity field, the particles preserve their motion direction, which allows for continuous separation like in infinite channels. For instance, Mutlu et al demonstrated the successful isolation of submicron particles and Staphylococcus aureus bacteria exploiting this approach [311]. However, the preparation of curved and wave-shaped microchannels might be challenging, and, for some applications, the straight microchannels are preferable due to the ease of preparation and parallelization.…”
Section: Inertial Focusing In Microfluidic Channelsmentioning
confidence: 99%
“…Due to the symmetry of the velocity field, the particles preserve their motion direction, which allows for continuous separation like in infinite channels. For instance, Mutlu et al demonstrated the successful isolation of submicron particles and Staphylococcus aureus bacteria exploiting this approach [311].…”
Section: Inertial Focusing In Microfluidic Channelsmentioning
confidence: 99%
“…Recently, oscillatory flows have been used to eliminate the need for long microchannel lengths and successfully applied to the inertial focusing of particles down to 500 nm (49). However, the use of oscillatory flows to manipulate species below this size is still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of oscillatory flows to manipulate species below this size is still unexplored. Mutlu et al have demonstrated that oscillatory inertial microfluidics can be used to focus particles in low Reynolds number regimes (one order of magnitude less than steady-flow inertial microfluidics) (49), however, the efficient focusing of species with dimensions below 100 nm would require microchannels with reduced dimensional cross-sections and channel lengths (on the order of few millimeters or microns) to allow access to high flow velocities. Although, such structures have been fabricated in rigid epoxy (42) or silicon (50) for example, system complexity and cost are unavoidably increased.…”
Section: Introductionmentioning
confidence: 99%